Proses Penanganan Ship To Ship (STS) Muatan Curah Kering Batubara Kapal MV. Ammar Oleh PT. Peayaran Bahtera Adhiguna Cabang Padang - Muhammad Hafiz; Suratni Ginting; Yusnidah Yusnidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose and objective of writing this paper is to understand the process of handling ship to ship (STS) dry bulk cargo of coal on MV. Ammar by PT. Peayaran Bahtera Adhiguna Padang Branch and the methods applied are the method (Library Research) and the fied method (Fied Study) by accuratey describing the Ship to Ship (STS) handling process for dry bulk coal cargo on the MV.Ammar which is carried out by PT. Peayaran Bahtera Adhiguna Padang Branch, where first make a Ship to Ship permit letter to the Harbor Master, permission to lift excavator heavy equipment to the Peindo pier and make a work order for the loading and unloading labor cooperative and if everything has been completed with permits for the inaportnet system and the fhinnisi system then Ship to Ship activities can begin. This paper also explains the obstacles faced, namey deays in submitting documents reated to the Ship To Ship (STS) process..